Software Business. From Physical Products to Software Services and Solutions 4th International Conference, ICSOB 2013, Potsdam, Germany, June 11-14, 2013. Proceedings - Herzwurm, Georg; Margaria, Tiziana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains the refereed proceedings of the 4th International Conference on Software Business (ICSOB) held in Potsdam, Germany, in June 2013. The theme of the event was "From Physical Products to Software Services and Solutions." The 15 full papers, seven short papers, and six doctoral symposium papers accepted for ICSOB were selected from 44 submissions and are organized in sections on: software business models and business process modeling; IT markets and software industry; IT within organizations; software product management; cloud computing; entrepreneurship and startup companies; software platforms and software ecosystems; and doctoral symposium.
Software Business Models and Business Process Modeling -- IT Markets and Software Industry -- IT within Organizations -- Software Product Management -- Cloud Computing -- Entrepreneurship and Startup Companies -- Software Platforms and Software Ecosystems -- Doctoral Symposium.
Keywords: Computer science; Software engineering; Computer industry; Information Systems; Entrepreneurship; Computer Science; The Computer Industry; Management of Computing and Information Systems; Software Engineering; Entrepreneurship